The Five Dimensions of Digital Technology Assessment with the Focus on Robotic Process Automation (RPA) - Axmann, Bernhard (Array, 2021)
In Technology Management, the assessment of new digital technologies is a challenging process. Most assessments are focusing on cost & benefit. These approaches often fail because main points are neglected. In this paper, the holistic approach of "The Five Dimensions of Digital Technology Assessment" will be described with the example of RPA (Robotic Process Automation). RPA is one of the most promising technologies to save data processing efforts in the office. The Five Dimensions of RPA Assessment is performed by assessing the benefits, technology readiness, usability, company readiness, and the costs that burden the company in the RPA implementation.